Manajemen Rantai Pasok Jamur Tiram di Kota Denpasar - Wibawa, Made Satria; Ambarawati, I Gusti Agung Ayu Anik; Suamba, Ketut (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol 4 No 1 (2016), 2016)
The demand for oyster mushroom in Denpasar today is quite high, but it cannot be fulfilled yet. Management of information, products, and financial flow in a supply chain is needed to meet the consumer demand of this product. This study aims to determine the mechanism and performance of oyster mushrooms supply chain in Denpasar. Respondents in this sudy were chosen purposively including baglog suppliers and farmers, mean while of respondents marketing agencies were selected using snowball sampling. Data obtained were analyzed using descriptive qualitative and marketing efficiency. Research results show that the oyster mushroom supply chain involving baglog suppliers, farmers, sub-district traders, retailers, processing traders and end consumers of processed has operated quite well. The flows including in the supply chain are product, financial, and information. Performance measurement results show that the most commonly marketing channel of fresh oyster occurs is involvement of farmers - retailer - consumer. This marketing channel is more efficient compared to other marketing channels. Based on the marketing margin analysis, it shows the  marketing margin of Rp 5,857, farmer' share at 76 percent, and the ratio of profit to the marketing cost is 6.58.
Keywords: oyster mushrooms, management, supply chain